STRATEGI DIPLOMASI EKONOMI INDONESIA DALAM MENGHADAPI PANDEMI COVID-19 - Aloysius Anandyo Pambudi (Universitas Jenderal Ahmad Yani, 2021)
The Covid-19 outbreak has caused a multi-sector global crisis on health, social, economic, and leadership aspects. Indonesia, as one of the Asia-Pacific countries which had significant economic growth for the last decade, is also facing a huge economic and social decline due to this pandemic. In order to face these challenges, the Indonesian government changed its economic diplomacy strategy by issued some policies regarding to upheld the national export-import performance and hold the negative economic impacts of the outbreak. This article provides a comprehensive analysis and descriptions about Indonesia’s economic diplomacy strategies in facing the Covid-19 pandemic. By adopting an analytical framework of economic diplomacy, this research shows that Indonesia’s government economic diplomacy strategies during the Covid-19 pandemic exist in both primary and support activities, consisting of commercial and marketing activities, business advocation, network-building, business negotiations, intelligence services, and also problem-solving mechanisms.